Bovine NK-lysin peptides exert potent antimicrobial activity against multidrug-resistant Salmonella outbreak isolates - Rohana P. Dassanayake (Nature Portfolio, 2021)
Abstract Multidrug-resistant (MDR) Salmonella is a threat to public health. Non-antibiotic therapies could serve as important countermeasures to control MDR Salmonella outbreaks. In this study, antimicrobial activity of cationic α-helical bovine NK-lysin-derived antimicrobial peptides was evaluated against MDR Salmonella outbreak isolates. NK2A and NK2B strongly inhibited MDR Salmonella growth while NK1 and NK2C showed minimum-to-no growth inhibition. Scrambled-NK2A, which is devoid of α-helicity but has the same net positive charge as NK2A, also failed to inhibit bacterial growth. Incubation of negatively charged MDR Salmonella with NK2A showed increased Zeta potential, indicating bacterial-peptide electrostatic attraction. Confocal and transmission electron microscopy studies revealed NK2A-mediated damage to MDR Salmonella membranes. LPS inhibited NK2A-mediated growth suppression in a dose-dependent response, suggesting irreversible NK2A-LPS binding. LPS-NK2A binding and bacterial membrane disruption was also confirmed via electron microscopy using gold nanoparticle-NK2A conjugates. Finally, NK2A-loaded polyanhydride nanoparticles showed sustained peptide delivery and anti-bacterial activity. Together, these findings indicate that NK2A α-helicity and positive charge are prerequisites for antimicrobial activity and that MDR Salmonella killing is mediated by direct interaction of NK2A with LPS and the inner membrane, leading to bacterial membrane permeabilization. With further optimization using nano-carriers, NK2A has the potential to become a potent anti-MDR Salmonella agent.